The Relationship Between Length of Stay (LOS) and Patient Satisfaction With Hospitality Services at Haji General Hospital Medan - Titin Nasiatin; Mukhlasin Mukhlasin (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
The length of stay (LOS) or duration of hospitalization is a key indicator of hospital service quality. Prolonged LOS often signals inefficiencies and can lead to lower patient satisfaction. The core issue in this study is the high percentage of patients dissatisfied with services at the Haji General Hospital Medan citing unresponsive staff and inadequate facilities. This research aims to determine the relationship between LOS and patient satisfaction following hospitalization. A quantitative research method with a cross-sectional design was employed. The study took place at Haji General Hospital Medan, North Sumatra, from January to May 2023. The population included 60 patients treated in the Jabal Rahma and Safa wards, with a purposive sample of 35 respondents who met the inclusion criteria. Data were gathered through questionnaires and medical record observations. Patient satisfaction was measured using a validated Likert-scale questionnaire, while LOS was recorded from hospital records. Data analysis was conducted using the Chi-square test. Results revealed that 57.1% of patients had a LOS of less than five days, and 60.0% reported being very satisfied with their care. Statistical analysis showed a significant relationship between LOS and patient satisfaction (p = 0.005 < 0.05). Shorter LOS was correlated with higher satisfaction levels, suggesting more effective medical performance. In conclusion, patients with shorter hospital stays tended to report greater satisfaction, highlighting LOS as a crucial factor in evaluating healthcare service quality. It is recommended that hospitals strive to optimize care efficiency without compromising outcomes. Further research is suggested to explore additional factors affecting satisfaction, such as staff communication and facility adequacy, to improve service delivery Keywords: Length of Stay (LOS), Patient Satisfaction, Hospitalization, Healthcare Quality.